2017
DOI: 10.1155/2017/2412486
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 G2019S Mutation: Prevalence and Clinical Features in Moroccans with Parkinson’s Disease

Abstract: Background. The LRRK2 G2019S mutation is the most common genetic determinant of Parkinson's disease (PD) identified to date. This mutation, reported in both familial and sporadic PD, occurs at elevated frequencies in Maghreb population. In the present study, we examined the prevalence of the G2019S mutation in the Moroccan population and we compared the motor and nonmotor phenotype of G2019S carriers to patients with idiopathic Parkinson's disease. Methods. 100 PD patients were assessed for motor and nonmotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 45 publications
4
36
1
Order By: Relevance
“…All patients agreed to participate and were recruited from October 2013 to June 2016 according to criteria described earlier [17]. Age at examination ranged from 35 to 86 years old and the mean age was 59 ± 11.4 years.…”
Section: Methodsmentioning
confidence: 99%
“…All patients agreed to participate and were recruited from October 2013 to June 2016 according to criteria described earlier [17]. Age at examination ranged from 35 to 86 years old and the mean age was 59 ± 11.4 years.…”
Section: Methodsmentioning
confidence: 99%
“…Kachergus and collaborators identified the G2019S mutation in 2005 (Kachergus et al., ), known as the most prevalent pathogenic mutation in LRRK2 that accounts for 5%–6% of autosomal‐dominant familial cases and 1%–2% of de novo generic PD cases in some Western populations (Gilks et al., ; Healy et al., ). The prevalence can be much higher depending on the population: a recent report suggested that as many as 70% of late‐onset PD patients seen at a neurology clinic in Morocco were positive for G2019S (Bouhouche et al., ). However, in far‐east Asian populations, the frequency of pathogenic LRRK2 mutations is extremely low (Tan et al., , ; Wu et al., ; Zabetian et al., ).…”
Section: Lrrk2 and The Kinase Hypothesis Of Lrrk2‐linked Pdmentioning
confidence: 99%
“…Leucine rich repeat kinase 2 (LRRK2) is a good target to improve our knowledge of these underlying processes as mutations within this protein are the most common cause for genetically driven forms of PD (5,6). LRRK2 is a complex and multifunctional protein consisting of seven closely interacting structural domains (7,8).…”
Section: Introductionmentioning
confidence: 99%